Pathogen presence, prevalence, and diversity in Ixodes scapularis and mammal hosts at their expanding northern range limits - Crandall, Kirsten E.; Kerr, Jeremy T.; Millien, Virginie (Frontiers in Parasitology, 2024)
With climate and land use changes, tick-borne pathogens are expected to become more widely distributed in Canada. Pathogen spread and transmission in this region is modulated by changes in the abundance and distribution of tick and host populations. Here, we assessed the relationships between pathogens detected in Ixodes scapularis and mammal hosts at sites of different levels of disease risk using data from summer field surveys in Ontario and Quebec, Canada. Generalized linear mixed models and ordinal logistic regressions were used to determine the influence of the abundance of I. scapularis and the abundance and diversity of mammal hosts on pathogen presence, prevalence, and diversity. We detected three pathogen species in I. scapularis and small mammals using nested PCRs, namely Borrelia burgdorferi sensu stricto, Babesia odocoilei, and Babesia microti. Depending on the analyzed pathogen, local infection prevalence ranged from 0% to 25.4% in questing ticks and from 0% to 16.7% in small mammal hosts. We detected B. odocoilei in localities beyond its known range limits in southeastern Quebec suggesting ongoing range expansion of this pathogen. Neither the abundance of I. scapularis nor the abundance and diversity of mammal hosts altered local pathogen presence and prevalence, contrary to expectations. However, mammal species richness was a key predictor of the number of pathogen species. Our study demonstrates the need for future surveillance efforts that test questing and feeding I. scapularis of all life stages, as well as their hosts to better determine the spread, transmission, and co-occurrence of tick-borne pathogens in Canada.